Delignifikasi Pelepah Daun Sawit Akibat Penambahan Urea, Phanerochaete chrysosporium, Dan Trametes sp. terhadap Kadar Abu, Kadar Protein, Kadar Lemak dan Bahan Ekstrak Tanpa Nitrogen (BETN) - Budi Kurniawan; Farida Fathul; Yusuf Widodo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2012)
Oil palm ribs plantations are less utilized. This is due to stem oil is tough stems, leaf spiked, and contains a stick that has a low digestibility values​​. The low digestibility is caused by the bonds between lignin and carbohydrates that can not be utilized by ruminants. Utilization of oil palm ribs as feed material is still limited because of the high lignin content of the low digestibility, requiring the application of technology to improve the nutritional value and digestibility of the stem oil. One way to do this is with the addition of urea, fungi Phanerochaete chrysosporium and Trametes sp into the oil palm ribs. The aim of this research is to know the proximate content and the best oil palm ribs processing as the result of the adding or urea, Phanerochaete crysosporium, and Trametes sp. to the content of ash, protein, fat, and NNE (Non Nitrogen Extract). This trial used Completly Rondomizes Design (CRD) with 3 replications. The data obtained was analized by using varience analysis on the test level of 5% or 1%, then continued by Least Significant Different (LSD). The best treatment on this trial was the fermentation of oil palm ribs + Trametes sp. Keywords: oil palm ribs, Lignin, Urea, Phanerochete chrysosporium, Trametes sp.